Anomalous Aortic Origin of the Right Pulmonary Artery From the Ascending Aorta With Spontaneous Dissection and Thrombosis. Issue 4 (July 2020) - Said, Sameh M.; Marey, Gamal; Brown, Nicholas M.; Griselli, Massimo; Rodgers, Nathan; Zupfer, Elena H.; Aggarwal, Varun; Hiremath, Gurumurthy M.
Anomalous aortic origin of the pulmonary artery is rare. It can affect either of the main branches and can be an important cause of neonatal respiratory distress. Early diagnosis and surgical repair is associated with improved survival and long-term outcomes.